2013
DOI: 10.5901/ajis.2013.v2n3p445
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Traditional English Language Testing in Thailand

Abstract: This study investigates students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…For this purpose, the alignment gains importance considering the frequently used items between the coursebook and TEPSE English tests. The analyses of both the coursebook and the English tests in TEPSE show that most of the frequently used items in the tests were also the ones used frequently in the coursebook, which was also emphasized with a similar finding obtained in the study of Jaturapitakkul (2013) which revealed content validity of the traditional English language tests in Thailand by focusing on the alignment between the tests and the content that the students learnt in the classroom. Moreover, the consistency between the coursebook and TEPSE English tests affects content validity positively as it was also emphasized in the studies of Aksan (2001) and Kang and Chang (2014).…”
Section: Alignment Between the Coursebook And Tepse English Tests Based On The Frequently Used Itemssupporting
confidence: 69%
See 2 more Smart Citations
“…For this purpose, the alignment gains importance considering the frequently used items between the coursebook and TEPSE English tests. The analyses of both the coursebook and the English tests in TEPSE show that most of the frequently used items in the tests were also the ones used frequently in the coursebook, which was also emphasized with a similar finding obtained in the study of Jaturapitakkul (2013) which revealed content validity of the traditional English language tests in Thailand by focusing on the alignment between the tests and the content that the students learnt in the classroom. Moreover, the consistency between the coursebook and TEPSE English tests affects content validity positively as it was also emphasized in the studies of Aksan (2001) and Kang and Chang (2014).…”
Section: Alignment Between the Coursebook And Tepse English Tests Based On The Frequently Used Itemssupporting
confidence: 69%
“…Nicholson (2015), who analyzed the TOEIC exam in Korea, found that content validity of the exam was weak because it did not test real communicative language skills. Even though the results of the several studies reviewed indicated low or lack of content validity of language exams, other studies (Ing et al, 2015;Jaturapitakkul, 2013;Kang &Chang, 2014;Külekçi, 2016) indicated high content validity in several other language tests. Ing et al (2015), Kang andChang (2014), andSim (2015) focused on the exams which were content valid besides the using the table of specifications.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the general situation of English language testing in Thailand, Jaturapitakkul's (2013) research revealed that the traditional static assessment still existed as a dominant method in most English language classrooms. Meanwhile, a shift to an innovation of the classroom assessment was called for by a number of Thai scholars (Darasawang & Reinders, 2015).…”
Section: Using Da To Improve the Efl Students' Speaking Skillmentioning
confidence: 99%